داعیانہ شخصیت سازی؛ نوجوانان عصر حاضر كی عملی رہنمائی كا بنیادی اصول(سیرت طیبہ كی روشنی میں): Self-development; A basic tool for Islamic Orientation of Youth"(In the Light of Seerah) - Dr. Hafiz Ahmad Hamaad; Dr. Muhammad Mansha Tayyab (MEI, 2023)
Manpower is one of the greatest assets of any country and the most important part of this asset is the youth, for it is a force that can overcome the problems of life and progress beyond the difficult and rough pathways. One ends childhood by entering into the phase of youth, the phase of personal responsibilities and social and public duties. Therefore, the world today pays special attention to young people and they have gained a special position in all affairs, including political, social, economic, industrial and moral. For the last fourteen centuries, the holy religion of Islam, within its comprehensive, revivalist program, has paid special, unique attention to the young generation. Islam makes provision for young people in all material, spiritual, psychological, educational, moral, social, worldly and otherworldly matters while other religions and cultures only consider certain aspects of the world of the young. In this article that methodology will be discussed which adopted by the Holy Prophet and He produced well-mannered youth in all aspects and also His saying about youth will be discussed to guide today’s trainer and youth as well.